Espectros da morte em duas narrativas de Thomas Bernhard: O náufrago e Árvores abatidas - uma provocação - Santos, José Lucas; Maas, Wilma (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/Programa de Pós-Graduação em Língua e Literatura Alemã, 2019)
Abstract In the novels of the Austrian writer Thomas Bernhard, the death of someone close to the narrator serves as a motive for him to begin the account of his memories. Our objective is to verify how the statute of death configures the literary space in two of Bernhard’s works, The loser (1983) and Woodcutters (1984). Considering that death occurs through suicide in these novels, it will be used as a theoretical foundation: The Seminar: book X - Anxiety, a book in which Jacques Lacan points to suicide (or passage to the act) as a form found by a subject to leave a scene they could no longer endure through words. Thereby, we will approach how the contact with death reverberates in the narrator’s subjectivity, inasmuch as death also is responsible for his return to Austria, a country from where he has always tried to disentangle himself.

Resumo Nos romances do escritor austríaco Thomas Bernhard, a morte de alguém próximo ao narrador serve de motivo para que este inicie o relato de suas memórias. Nossa proposta é verificar como o estatuto da morte configura o espaço literário de duas obras de Bernhard, a saber, O náufrago (1983) e Árvores abatidas - uma provocação (1984). Considerando que, nesses romances, a morte se dá pela via do suicídio, utilizaremos como fundamentação teórica o Seminário 10 - A angústia, livro em que Jacques Lacan aponta o suicídio (ou passagem ao ato) como uma forma encontrada pelo sujeito para sair de uma cena a qual ele não conseguiria mais sustentar pela palavra. Desse modo, abordaremos como o contato com a morte reverbera na subjetividade do narrador, já que a morte também é responsável por seu retorno à Áustria, país de onde ele sempre tentara se desvencilhar.
The specter of death in two of Thomas Bernhard’s narratives: The loser and Woodcutters
Keywords: Thomas Bernhard; narrator; death; suicide; Thomas Bernhard; narrador; morte; suicídio